\(4\frac{1}{3}:\frac{x}{4}=6:0,3\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 8 2018

\(\frac{13}{3}:\frac{x}{4}=6:0,3\)

\(\frac{13}{3}:\frac{x}{4}=20\)

         \(\frac{x}{4}=\frac{13}{3}:20\)

         \(\frac{x}{4}=\frac{13}{3.20}\)

         \(\frac{x}{4}=\frac{13}{60}\)

\(60x=13.4\)

\(60x=52\)

     \(x=\frac{52}{60}\)

     \(x=\frac{13}{15}\)

Vậy \(x=\frac{13}{15}\)

25 tháng 8 2019

mk cs kq r

25 tháng 8 2019

chờ tí

19 tháng 8 2020

\(\frac{13}{3}:\frac{x}{4}=6:0,3\)

\(\frac{13}{3}:\frac{x}{4}=20\)

\(\frac{x}{4}=\frac{13}{3}:20\)

\(\frac{x}{4}=\frac{13}{60}\)

x.60:=4.13

x.60=52

x=52:60

\(x=\frac{13}{15}\)

vậy \(x=\frac{13}{15}\)

19 tháng 8 2020

\(4\frac{1}{3}:\frac{x}{4}=6:0,3\)

\(\Rightarrow\frac{13}{3}.\frac{4}{x}=20\)

\(\Rightarrow\frac{4}{x}=\frac{60}{13}\)

\(\Leftrightarrow60x=13.4=52\)

\(\Leftrightarrow x=\frac{13}{15}\)

26 tháng 10 2020

a) \(\frac{-3}{7}+x=\frac{1}{3}\)

\(\Leftrightarrow x=\frac{1}{3}+\frac{3}{7}\)

\(\Leftrightarrow x=\frac{16}{21}\)

b) \(\frac{-5}{8}+x=\frac{-2^2}{3}\)

\(\Leftrightarrow x=\frac{-4}{3}+\frac{5}{8}\)

\(\Leftrightarrow x=-\frac{17}{24}\)

c) \(4\frac{1}{3}:\frac{x}{4}=6:0,3\)

\(\Leftrightarrow\frac{8}{3}:\frac{x}{4}=20\)

\(\Leftrightarrow\frac{32}{3x}=20\)

\(\Leftrightarrow3x=\frac{8}{5}\)

\(\Leftrightarrow x=\frac{8}{15}\)

1 tháng 2 2017

\(1\frac{2}{3}:\frac{x}{4}=6:0,3\)

\(\frac{5}{3}:\frac{x}{4}=20\)

\(\frac{x}{4}=\frac{5}{3}:20\)

\(\frac{x}{4}=\frac{1}{12}\)

\(\Rightarrow\frac{3x}{12}=\frac{1}{12}\)

\(\Rightarrow3x=1\)

\(\Rightarrow x=\frac{1}{3}\)

Vậy \(x=\frac{1}{3}\)

16 tháng 7 2016

a)4,5:0,3=2,25:(0,1.x)

   2,25:(0,1.x)=15

   0,1.x=0,15

   x=0,15:0,1

   x=1,5

Vậy x=1,5

b)8:\(\left(\frac{1}{4}.x\right)\)=2:0,02

   8:\(\left(\frac{1}{4}.x\right)\)=100

       \(\left(\frac{1}{4}.x\right)\)=\(\frac{8}{100}\)

        x=\(\frac{8}{100}\):\(\frac{1}{4}\)

         x=\(\frac{8}{25}\)

Vậy x=\(\frac{8}{25}\)

c)\(3:2\frac{1}{4}=\frac{3}{4}:\left(6.x\right)\)

   \(\frac{3}{4}:\left(6.x\right)=\frac{4}{3}\)

    6.x=\(\frac{3}{4}:\frac{4}{3}\)

    6.x=\(\frac{9}{16}\)

    x=\(\frac{9}{16}\):6

    x=\(\frac{3}{32}\)

Vậy x=\(\frac{3}{32}\)

16 tháng 7 2016

a.

\(4,5\div0,3=2,25\div\left(0,1\times x\right)\)

\(2,25\div\left(0,1\times x\right)=15\)

\(0,1\times x=\frac{2,25}{15}\)

\(0,1\times x=0,15\)

\(x=\frac{0,15}{0,1}\)

\(x=1,5\)

b.

\(8\div\left(\frac{1}{4}\times x\right)=2\div0,02\)

\(8\div\left(\frac{1}{4}\times x\right)=100\)

\(\frac{1}{4}\times x=\frac{8}{100}\)

\(\frac{1}{4}\times x=\frac{2}{25}\)

\(x=\frac{2}{25}\div\frac{1}{4}\)

\(x=\frac{2}{25}\times4\)

\(x=\frac{8}{25}\)

c.

\(3\div2^1_4=\frac{3}{4}\div\left(6\times x\right)\)

\(\frac{3}{4}\div\left(6\times x\right)=3\div2,25\)

\(\frac{3}{4}\div\left(6\times x\right)=\frac{4}{3}\)

\(6\times x=\frac{3}{4}\div\frac{4}{3}\)

\(6\times x=\frac{3}{4}\times\frac{3}{4}\)

\(6\times x=\frac{9}{16}\)

\(x=\frac{9}{16}\div6\)

\(x=\frac{9}{16}\times\frac{1}{6}\)

\(x=\frac{3}{32}\)

14 tháng 7 2016

làm 1 bài mẫu nha

a) \(\left(\frac{1}{3}.x\right):\frac{2}{3}=\frac{25}{6}\)

\(\Rightarrow\frac{1}{3}x=\frac{25}{9}\)

\(\Rightarrow x=\frac{25}{9}:\frac{1}{3}\)

\(\Rightarrow x=\frac{25}{3}\)

các bài sau dễ lắm

a) \(\left(\frac{1}{3}x\right):\frac{2}{3}=1\frac{2}{3}:\frac{2}{5}\)

\(\Rightarrow\frac{1}{3}x:\frac{2}{3}=\frac{25}{6}\)

\(\Rightarrow\frac{1}{3}x=\frac{5}{3}\)

\(\Rightarrow x=\frac{5}{3}:\frac{1}{3}\)

\(\Rightarrow x=5\)

28 tháng 10 2020

a, ( 152 +và 2/4 - 148 và 3/8 ) : 0,2 = x : 0,3

=>  33/8 : 1/5 = x : 3/10

=>  x : 3/10 = 165/8

=>  x = 99/10

b, ( 85 và 7/30 - 83 và 5/18 ) : 2 và 2/3 = 0,01x : 4

=>  88/45 : 8/3 = 0,01x : 4

=> 0,01x : 4 = 11/15

=> 0,01x = 44/15

=> x = 880/3

c, x - 1/ x + 5 = 6/7

=> 7( x - 1 ) = 6( x + 5 )

=> 7x - 7 = 6x + 30

=> 7x - 6x = 7 + 30

=> x = 37

d, x2/6 = 24/25

=> x2. 25 = 6 . 24

=> x2.25 = 144

=> x2 = 144/25

=> x = ( 12/5)2 hoặc x = ( -12/5)

g, x - 3/ x + 5 = 5/7

=> 7( x - 3 ) = 5 ( x + 5 )
=> 7x - 21 = 5x + 25

=> 7x - 5x = 21 + 25

=> 2x = 46

=> x = 23